2004
DOI: 10.1007/s00347-003-0902-3
|View full text |Cite
|
Sign up to set email alerts
|

Die Struktur der Extrazellul�rmatrix bei Keratokonus

Abstract: The changes point on deregulation of the matrix arrangement. The interest in the cause of the disease is focused on the interfibrillar arrangement, the interaction between collagen and proteoglucanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
0
5
0
4
Order By: Relevance
“…Collagen type IV α1/α2 chains have been reported in KC patients [34], while COL4A1 has been shown to be down-regulated in KC corneas [35]. The chromosomal loci of COL4A1 and COL4A2 are close to 13q32 [32], with the COL4A1 gene consisting of 52 exons and COL4A2 gene of 48 exons [28].…”
Section: Resultsmentioning
confidence: 99%
“…Collagen type IV α1/α2 chains have been reported in KC patients [34], while COL4A1 has been shown to be down-regulated in KC corneas [35]. The chromosomal loci of COL4A1 and COL4A2 are close to 13q32 [32], with the COL4A1 gene consisting of 52 exons and COL4A2 gene of 48 exons [28].…”
Section: Resultsmentioning
confidence: 99%
“…Assuming a corneal thickness of 500 mm, the anterior 200 mm had an area portion of 0.4 and a remainder of 0.6; therefore, the stress of the whole cornea can be calculated by s Z 0.4 Â s 200 C 0.6 Â s po (s 200 Z stress in the anterior 200 mm; s po Z stress in the posterior cornea). Stachs et al 19 found an irregular structure of keratocytes only in the anterior stroma of keratoconic cornea by confocal laser-scanning microscopy, which is of great importance because this part is mainly responsible for corneal rigidity. New electron microscopic and X-ray scattering measurements have found a lack of obliquely oriented anterior-to-posterior lamellae crossing or interweaving the stress-bearing lamellae in the anterior stroma of keratoconic corneas.…”
Section: Discussionmentioning
confidence: 99%
“…Die Bildung des kornealen Apex ist verbunden mit einer Verlagerung der Achsen der Kollagen-Fibrillen und einer Drehung der orthogonalen Matrix [52]. Dadurch kommt es zu einer Veränderung des Quervernetzungsgrades der Hornhaut mit daraus folgender reduzierter mechanischer Stabilität [70]. Ursächlich ist vermutlich eine veränderte interfibrilläre Matrix, die im Bereich der kornealen Lamellenbildung zu einer veränderten Lamellenstruktur führt und die durch eine Deregulation der Kollagene und Proteoglykane erklärt werden kann.…”
Section: Struktur Der Kollageneunclassified
“…Zwei unabhängige Studien beschreiben ein Auftreten eines Mitralklappenprolaps in Zusammenhang mit einem Keratokonus in 44 -58 %. Diese beiden Studien legen die Verbindung eines Keratokonus mit einer Fehlexpression eines Kollagens nahe [7,70]. In einer größeren Studie konnte dieser Zusammenhang jedoch nicht belegt werden [74].…”
Section: Mitralklappenerkrankungenunclassified